2012
DOI: 10.4097/kjae.2012.62.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous psoas compartment block and intravenous patient controlled analgesia on postoperative pain control after total knee arthroplasty

Abstract: BackgroundTotal knee arthroplasty (TKA) generates severe postoperative pain in 60% of patients and moderate pain in 30% of patients. Because inadequate postoperative pain control can hinder early physiotherapy and rehabilitation, it is the most influential factor dictating a good outcome. The purpose of this study was to evaluate the effectiveness of continuous psoas compartment block (PCB) in comparison to intravenous patient-controlled analgesia (IVPCA) in TKA patients.Methods40 TKA patients were randomly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Of note, the authors did not find any difference in length of hospital stay, satisfaction, or rescue emetic use. 66 These favorable outcomes have similarly been shown when compared to other regional blocks. In a study by Kaloul et al comparing lumbar plexus block with a three-in-one FNB, they found simi-lar reductions in 48 hour opioid consumption, similar pain scores at six and 24 hours post operatively, but a greater sensory and motor blockade of the obturator nerve in the lumbar plexus group.…”
Section: Lumbar Plexus Nerve Blockmentioning
confidence: 68%
See 2 more Smart Citations
“…Of note, the authors did not find any difference in length of hospital stay, satisfaction, or rescue emetic use. 66 These favorable outcomes have similarly been shown when compared to other regional blocks. In a study by Kaloul et al comparing lumbar plexus block with a three-in-one FNB, they found simi-lar reductions in 48 hour opioid consumption, similar pain scores at six and 24 hours post operatively, but a greater sensory and motor blockade of the obturator nerve in the lumbar plexus group.…”
Section: Lumbar Plexus Nerve Blockmentioning
confidence: 68%
“…64,65 In a paper by Lee et al, similar pain scores were recorded in comparison to patients with intravenous patient controlled analgesia, after a total knee arthroplasty until after 6 hours post-operatively. 66 Though the PCB group reporting statistically significant improvements on pain, nausea, and sedation after 6 hours post operatively. 66 The authors postulated this difference in time was due to the anesthetics need to fully infiltrate the compartment before achieving full and optimal effect.…”
Section: Lumbar Plexus Nerve Blockmentioning
confidence: 89%
See 1 more Smart Citation
“…In clinical, we usually use PCIA, epidural analgesia and CFNB which owns different features. Lee et al (15) found that PCIA provided less better analgesia and more side effects such as nausea and sedation compared with continuous peripheral block. Patel et al (16) found peripheral nerve block was safe with a significant decrease in postoperative complications and provided adequate pain relief compared to epidural anesthesia CFNB and PCIA are two commonly used methods for postoperative analgesia after TKA.…”
Section: Discussionmentioning
confidence: 99%